PERAN SOSIAL EKONOMI KELOMPOK TANI PADI DALAM MENINGKATKAN KESEJAHTERAAN PETANI: WAWASAN DARI SINJAI, SULAWESI SELATAN - Pratama, Ahmad Aditya; Astaman, Putra; Raisa, Daeva Mubarika; Megawati, Megawati (Jurnal Riset Multidisiplin Agrisosco, 2025)
The purpose of this research is to determine the extent of the farmer groups' role in improving farmers' welfare. This study employs a quantitative descriptive method with data collected through observation, interviews, documentation, and questionnaires involving 87 farmer group members. The analysis results indicate that the role of the farmer group falls into the “strongly active” category, reaching an index score of 78.67%. Based on the Importance Performance Analysis (IPA), two main priority attributes, four achievement attributes that need to be maintained, five low-priority attributes, and four excessive attributes were identified. Meanwhile, analysis using the Customer Satisfaction Index (CSI) shows a value of 68.87%, which indicates that farmers in Aska Village are satisfied with the services provided by the farmer group. However, performance improvements are still necessary to better meet the expectations and needs of the farmers.